СОВРЕМЕННЫЕ НАПРАВЛЕНИЯ ЯЗЫКОЗНАНИЯ В КЫРГЫЗСТАНЕ - Жоламанова, Е. И. (Eurasian Journal of Philology Science and Education, 2015)
Cognitive linguistics of Kyrgyzstan was presented to native science of language by such linguists as Z.K.Derbisheva, M.I.Lasaridi, M.D.Tagaev and is developing since of ХХI century. His research will be used to further language theory development in the modern course of linguistics.